Protocol for the process evaluation of a cluster randomised controlled trial evaluating the effectiveness and cost-effectiveness of a school-based intervention to prevent anxiety and depression in Malaysia: the MyHeRo study - Cecilia A., Essau; Suwaibah, Zakaria; Chuong Hock, Ting; Julia Ai Cheng, Lee; Alejandro de la, Torre-Luque; Alvin Lai, Oon Ng; Hazreen, Abdul Majid; Helen, Dodd; Nik Daliana, Nik Farid; Noor Azimah, Muhammad; Suzaily, Wahab (Taylor & Francis Group, 2025)
Process evaluations are essential for interpreting outcome trial results, offering insights into how and why interventions succeed or fall short across varying settings. this article outlines the protocol for a process evaluation embedded within the MyheRo cluster randomised controlled trial (RCt) assessing super skills for life (ssl), a school-based psychosocial programme in Malaysian secondary schools. given the multifaceted nature of ssl and the diversity of school environments, this evaluation explores how ssl is implemented and experienced in educational settings. a mixed methods approach will assess implementation, acceptability, and contextual factors influencing ssl delivery. Data will be collected through semi-structured interviews with school management, ssl facilitators, and participating adolescents, alongside direct observations of ssl sessions by trained independent assessors to examine fidelity, adherence, and participant engagement. Findings will be synthesised to understand how implementation processes may influence trial outcomes. the results will provide valuable insights into the delivery and reception of SSL in Malaysian schools, identifying barriers and facilitators to successful implementation. Findings will aid mental health professionals interpret trial findings and develop strategies for effectively integrating school-based mental health interventions that are scalable, sustainable, and responsive to local cultural and educational contexts.